Outcome of the public consultation on the draft Guidance of the EFSA PLH Panel on quantitative pest risk assessment. Issue 8 (3rd August 2018) - ,; Gilioli, Gianni; Hart, Andy; MacLeod, Alan; van der Werf, Wopke; Mosbach‐Schulz, Olaf; Stancanelli, Giuseppe; Vos, Sybren; Kozelska, Svetla
Abstract : EFSA has carried out a public consultation on the draft Guidance of the EFSA Scientific Panel on Plant Health (PLH Panel) on quantitative pest risk assessment with the aim of collecting input from the scientific community and all interested parties. The draft Guidance was prepared by the dedicated Working Group of the PLH Panel. It provides guidance on the methodology to conduct quantitative pest risk assessment and the evaluation of risk reduction options. The methodology consists of a two‐phase approach. Phase one consists of pest categorisation to determine whether the pest has the characteristics of a quarantine pest or those of a regulated non‐quarantine pest for the area of the EU. Phase two consists of pest risk assessment and is a more detailed assessment to inform phytosanitary decision making. Following the endorsement of the draft Guidance by the PLH Panel, the public consultation was launched on 12 February 2018 and closed on 25 March 2018. EFSA received 178 comments on the draft Guidance from 11 interested parties. This technical report on the outcome of the public consultation on the draft Guidance summarises the comments received through the public consultation and presents the responses of the PLH Panel to the comments. The PLH Panel prepared an updated version of the draft Guidance taking into account the comments received. The Guidance was adopted at the PLH Panel plenary meeting on 21 June 2018, and is published in the EFSA Journal. Abstract : This publication is linked to the following EFSA Journal article:http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2018.5350/full